2010
DOI: 10.3390/e12030326
|View full text |Cite
|
Sign up to set email alerts
|

Fuhrman, G. Rehabilitating Information. Entropy, 2010, 12, 164-196

Abstract: The author would like to change the phrase “the financial ‘meltdown’ of 1908” into “the financial ‘meltdown’ of 2008” on page 190 of the article. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, during the program they developed a better appreciation for the experiences students bring to the classroom. Fuhrman et al (2010) found graduate teaching assistants believed effective teachers exhibit passion for their subjects, are knowledgeable about and care for students, use a variety of teaching strategies, and help students appreciate the relevance of information to their own context. Sprinkle (2009) tested hypotheses regarding graduate students' perceptions of effective teaching, including teachers' age, gender, personality traits, and teaching style.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the program they developed a better appreciation for the experiences students bring to the classroom. Fuhrman et al (2010) found graduate teaching assistants believed effective teachers exhibit passion for their subjects, are knowledgeable about and care for students, use a variety of teaching strategies, and help students appreciate the relevance of information to their own context. Sprinkle (2009) tested hypotheses regarding graduate students' perceptions of effective teaching, including teachers' age, gender, personality traits, and teaching style.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graduate students often have teaching responsibilities, and they may be "most qualified to comment on teaching and its impact on learning because they can draw from recent and current experience" (Saroyan, Dangenais, & Zhou, 2009, p. 580). While extensive literature exists about students' perceptions of teaching effectiveness in K-12 education, not as much has been written about graduate students' perspectives on the subject (Fuhrman, Fuhrman, & DeLay, 2010 et al, 2009). Given the complex task of learning to teach, identifying traits indicative of effective teaching can be a constructive first step in helping students learn to teach.…”
mentioning
confidence: 99%